Training Analysis: A Historical View - Diego Sarracino; Marco Innamorati (Rivista Internazionale di Filosofia e Psicologia, 2012)
The obligatory nature of training analysis, i.e. of the personal analysis of every candidate analyst, was adopted by all psychoanalytic institutes in Freud’s lifetime. But what had initially been a not particularly burdensome addition to training was subsequently transformed into something quite different. Years of analysis: hundreds of hours at vast expense to the candidate, in the face of a basic unconcern on the part of the schools about undertaking empirical studies or even just examining more closely the theoretical justification (apart from the constantly reasserted need for completeness) for such a commitment. The considerable resistance to questioning this practice goes hand in hand with the persistent circulation of a series of legends about its origin. An accurate historical review should offer interesting matter for consideration, showing how the custom of requiring training analysis is underpinned by reasons of an institutional nature rather than by theoretical necessity or empirical findings.